Past in the Making - Kopeček, Michal (2008)
Historical revisionism, far from being restricted to small groups of ‘negationists,’ has galvanized debates in the realm of recent history. The studies in this book range from general accounts of the background of recent historical revisionism to focused analyses of particular debates or social-cultural phenomena in individual Central European countries, from Germany to Ukraine and Estonia. Where is the borderline between legitimate re-examination of historical interpretations and attempts t...